Pendekatan Pembelajaran Berbasis Masalah Untuk Meningkatkan Hasil Belajar Siswa Kelas VII B SMP Negeri 1 Towuti Kabupaten Luwu Timur - Adriana, Adriana (Universitas Negeri Makassar, 2018)
This study aims to improve the learning outcomes of mathematical concepts through a problem-based learning approach on the students class VII.B State Junior High School 1 Towuti East Luwu Regency. The type of research is classroom action research. The subjects of the study were students of class VII.B State Junior High School 1 Towuti is 32 people. Data were collected using observation, written tests, and documentation, while the data of the research are analyzed descriptively. The results showed that the mathematics learning outcomes of the set of concepts increased through the problem-based learning approach. In Cycle I, the mathematics learning outcomes of the set of sets in either category (average 71.25) or 53.12 percent. In Cycle II, the results ofÂ mathematics learning increased to very good category (average 85.47) and reached learning mastery criteria is 90.62 percent. The improvement of mathematics learning outcomes is supported by the improvement of student learning activities, such as: liveliness to pay attention to teacher explanation, recording set material, solve group problem, question with friend and teacher in the solution of the set problem, and to conclude the set matter